Corporate social investment practices as ‘soft technology’: A case of selected Botswana firms - Maunganidze, Langtone (Elsevier, 2022)
The study on which this article is based sought to examine the motives and patterns of corporate social investment practices using the experiences of eight Botswana Stock Exchange listed firms. It followed an exploratory sequential mixed-methods design utilizing a triangulation of documentary and archival records, and cross-sectional survey techniques. The study found out that although the motives for the practices were varied they were largely reactive and fragmented, and mostly driven by economic rather than business ethics imperatives. The article supports extant literature indicating the existence of growing publics' disillusionment with the apparent dissonance between corporates' historical institutional rhetoric and practice. Although the firms publicly portrayed themselves as good corporate citizens addressing wider societal challenges, in practice they engaged in the traditional ‘giving back to community’ donations. The article concludes that overall the practices served as ‘soft technologies’ for the (re)-figuration of corporate identities.